2018
DOI: 10.1186/s13756-018-0343-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental colonization and onward clonal transmission of carbapenem-resistant Acinetobacter baumannii (CRAB) in a medical intensive care unit: the case for environmental hygiene

Abstract: BackgroundIn May 2015, we noticed an increase in carbapenem-resistant Acinetobacter baumannii (CRAB) infections in the Medical Intensive Care Unit (MICU). To investigate this, we studied the extent of environmental contamination and subsequent onward clonal transmission of CRAB.MethodsWe conducted a one-day point prevalence screening (PPS) of the patients and environment in the MICU. We screened patients using endotracheal tube aspirates and swabs from nares, axillae, groin, rectum, wounds, and exit sites of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The environment surrounding seventy of these patients demonstrated contamination across all study days [38]. In another study investigating the environmental contamination of CRAB in an endemic setting, investigators found that ICU rooms occupied by patients carrying CRAB were consistently colonized by genomically similar strains of CRAB [39]. The investigators also demonstrated persistence of CRAB in the environment and subsequent clinical infection, highlighting the need for carefully thought out IPC strategies to control MDRO in an endemic setting.…”
Section: Non-outbreak Reportsmentioning
confidence: 98%
See 1 more Smart Citation
“…The environment surrounding seventy of these patients demonstrated contamination across all study days [38]. In another study investigating the environmental contamination of CRAB in an endemic setting, investigators found that ICU rooms occupied by patients carrying CRAB were consistently colonized by genomically similar strains of CRAB [39]. The investigators also demonstrated persistence of CRAB in the environment and subsequent clinical infection, highlighting the need for carefully thought out IPC strategies to control MDRO in an endemic setting.…”
Section: Non-outbreak Reportsmentioning
confidence: 98%
“…A recent study by Mody et al [40] demonstrated that contamination of patients' hands with MDRO is frequent and correlates with contamination of high-touch surfaces. Patients who were colonized or infected with CRAB were also shown to have higher environmental contamination with clonal CRAB compared to patients who were not [39,41]. The higher burden of MDRGN as usually observed in clinical infections, has been shown to increase environmental contamination [42,43].…”
Section: Non-outbreak Reportsmentioning
confidence: 99%
“…Indeed, a recent study found A. baumannii isolates collected from the same individual to differ by as many as 11 SNPs. 22 However, the analysis presented here does not distinguish whether the outbreak was the result of expansion from a single strain or, less likely, the result of the introduction of multiple highly related strains (eg, from an environmental reservoir).…”
Section: Discussionmentioning
confidence: 91%
“…The size, shape and biovolume of bacteria may influence the filterability of a sample and potentially lead to inaccurate findings, particularly if multiple species of bacteria are being investigated using the one pore diameter [ 96 ]. Alternative molecular techniques for bacterial detection such as qPCR and whole-genome sequencing (WGS) have been employed by 27 studies included in this review [ 13 , 14 , 17 , 18 , 20 , 25 , 26 , 34 , 37 , 40 , 43 , 45 , 46 , 51 , 52 , 56 , 57 , 59 , 60 , 63 , 64 , 65 , 97 , 98 , 99 , 100 , 101 ]. Molecular techniques have significant advantages such as rapid turnaround times and detection of non-culturable cells [ 102 ].…”
Section: Discussionmentioning
confidence: 99%